Study on the effect of industrial structure transformation on regional ecological efficiency in ecological economic zone under carbon peaking and carbon neutrality strategy - Wang, Yan; Wang, Ladi (Frontiers in Environmental Science, 2022)
As the main strategy for the coordinated development of China's ecological economy in the future, the carbon peaking and carbon neutrality strategy is an important response strategy to solve the two major problems of China's urbanization process: the industrial structure is biased toward tradition and the economic development is biased toward high carbon. Under this development prospect, how to coordinate ecological development and economic development through the transformation of the industrial structure and form a unified development situation is an important issue for the development of the ecological economy. To solve this problem, the research starts with the theory of industrial structure change and ecological efficiency, puts forward two kinds of ecological efficiency assumptions, and establishes a mathematical model based on the C-D production function and cost function for the impact of industrial structure change on ecological efficiency. On this basis, a spatial model is formed, and empirical analysis is carried out for the important domestic ecological economic zone - the Yangtze River Economic Belt. The research results show that the industrial structure of the eco-economic zone will have a significant positive impact on ecological efficiency. At the same time, under the effect of inter-city cooperation, ecological efficiency has a significant spatial spillover effect. At the same time, the spatial lag factor and spatial error factor of urban agglomeration in the Yangtze River Delta are significant at the 10% and 5% levels, and the spatial lag factor and spatial error factor of urban agglomeration in the middle and long reaches are significant at the 5% level. It can be seen that the spatial dependence and linkage of ecological effects are strong, and there is a relatively significant interaction.